Identification of Nitrogen Starvation-Responsive miRNAs to Reveal the miRNA-Mediated Regulatory Network in Betula luminifera - Lin, Yan; Chu, Sasa; Xu, Xiaoshan; Han, Xiao; Huang, Huahong; Tong, Zaikang; Zhang, Junhong (Frontiers in Genetics, 2022)
Due to the immobility, plants encounter a series of stresses, such as varied nutrient concentration in soil, which regulate plant growth, development and phase transitions. Nitrogen (N) is one of the most limiting factors for plants, which exemplified by low nitrogen (LN) has a great adverse effect on plant growth and development. In the present study, we explored the potential role of microRNAs (miRNAs) in response to LN stress in Betula luminifera. We identified 198 miRNAs using sRNA sequencing, including 155 known and 43 novel miRNAs. Among them, 98 known miRNAs and 31 novel miRNAs were differentially expressed after 0.5h or 24h of LN stress. Based on degradome data, 122 differential expressed miRNAs (DEmiRNAs) including 102 known miRNAs and 20 novel miRNAs targeted 203 genes, comprising 321 miRNA-target pairs. A big proportion of target genes were transcription factors and functional proteins, and most of the GO terms were enriched in biological process, as well as one KEGG term “ascorbate and aldarate metabolism” was significantly enriched. The expression patterns of six miRNAs and their corresponding target genes under LN stress were monitored. According to the potential function for targets of DEmiRNAs, a proposed regulatory network mediated by miRNA-targets pairs under LN stress in B. luminifera was constructed. Taken together, these findings provide useful information to elucidate miRNA functions and establish a framework for exploring N signaling networks mediated by miRNAs in B. luminifera. It may provide new insights into the genetic engineering of high use efficiency of N in forestry trees.